Publicizing the results of standardized external tests: Does it have an effect on school outcomes? - Brindusa Anghel; Antonio Cabrales; Jorge Sainz; Ismael Sanz (IZA Journal of European Labor Studies, 2015)
We study the effect of standardized external tests on students' academic outcomes. We exploit the fact that only one of the 17 Spanish regions started doing and publishing the results of standardized tests in 2005 and apply a difference-in-difference methodology using outcomes of the PISA study from 2000 to 2009. We later confirm our results using synthetic control methods. Employing data from a single country allows us to minimize biases arising from differences in legal frameworks, social or cultural environments. Our econometric analysis lends plausibility to the hypothesis that this type of test significantly improves student outcomes. A key novelty is that our exams do not have academic consequences for the students, so effects have to come directly from the impact on teachers and administrators.
Keywords: I20; I21; 330; External and standardized tests; PISA; Difference-in-difference; Synthetic control methods